Immersive technologies and data as strategic tools for competitive banking products and prices - Silva, M. C.; Jerónimo, C. H.; Alturas, B. (Proceedings of 20th Iberian Conference on Information Systems and Technologies (CISTI 2025), 2026)
This research explores the integration of immersive technologies and advanced data analytics as strategic tools in banking, aiming to enhance competi-tive business models, efficient management and pricing and costs competitiveness. This study investigates the potential of immersive technologies, such as virtual reality and augmented reality, in creating immersive data-driven environments for decision-makers. The research examines how these technologies can improve risk assessment processes, foster more informed decision-making, and ultimately lead to the development of lower-risk banking products. Furthermore, the study delves into the utilization of big data analytics to extract actionable insights from vast datasets, enabling corporate banks to refine risk models and optimize pricing struc-tures. By leveraging immersive technologies and data analytics synergistically, the research aims to empower corporate banking institutions to offer more competitive and tailored financial products and services. The findings of this study contribute to the evolving landscape of corporate banking strategies, offering insights into innovative approaches for mitigating risks and enhancing market competitiveness in an ever-changing financial environment.